“Aquele que se fez, fez, aquele que não se fez, ficou por se fazer”: histórias e modos de vida de famílias deslocadas por um projeto de desenvolvimento no setor energético. - PEREIRA, Paula Marize Nogueira (2022)
This dissertation analyzes the effects of compulsory displacement of the Vila Madureira Community, displaced due to the installation of UTE Porto de Itaqui in the rural area of the Municipality of São Luís-MA and resettled in Vila Residencial Nova Canaã in the Municipal ity of Paço do Lumiar-MA , on the way of life of resettled families, considering the changes materialized from the implementation of the Residential Relocation Program proposed by the entrepreneurs. During the investigation, we adopted a qualitative approach, with the applica tion of semi-structured interviews, aiming to obtain data on the way of life of the families before and after the displacement, using the memory of the resettled to obtain information about life in the former location. Thus, it was found that, despite the entrepreneur's promise to ensure the integral reconstitution of the displaced families' ways of life, the resettlement mod el modified the various economic, social, cultural and religious practices and imposed new relationships between home, agricultural work and nature. Changing ways of life made fami lies more dependent on state and business action to maintain their livelihoods.